What Does the 2025 Budget Promise? - Gubad Ibadoghlu (SSRN, 2024)
This article provides a comparative analysis of the main parameters of the 2025 state budget with those of neighboring countries. It examines the structural and trend analysis of budget revenue sources and expenditures while also evaluating the expectations of consumers, businesses, and state organizations for the 2025 budget. Additionally, the article identifies weaknesses in the upcoming state budget, assessing budget oversight regarding transparency and public participation. The relationship between the parliament and the executive branch during the allocation of budget expenditures and its impact on budget management is also discussed. Specific and institutional risks that may affect budget implementation and the corruption potential of the 2025 state budget are evaluated.
Keywords: 330; Azerbaijan; budget; revenue; expenditures; transparency; accountability; public participation; corruption